Octahedral BIF-29 catalytic material as well as continuous preparation method and application thereof
By developing octahedral BIF-29 catalytic material, using its unique M6L8 structure and copper-nitrogen bond, the insulation limitations of existing MOFs in electrocatalytics and the problem of heat treatment in traditional copper-based MOFs is achieved, and efficient carbon dioxide electricity is achieved Catalytic reduction, catalytic performance has been significantly improved.
Patent Information
- Application Number
- CN202411417816.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing metal organic frame (MOFs) materials are limited by their insulating properties in terms of electrocatalysis, making it difficult to effectively catalyze the reduction of carbon dioxide, resulting in slow kinetics of the electrocatalytic process. Traditional copper-based MOFs require heat treatment, and the structure is prone to deformation, affecting the catalytic performance. .
Developed an octahedral BIF-29 catalytic material with an M6L8 structure and six exposed single-core copper centers, prepared by a microfluidic pneumatic continuous reaction device, and a cage-like structure formed by copper-nitrogen bonds is used as a high-efficiency electrocatalyst. It is used directly for The electrocatalytic reduction of carbon dioxide avoids heat treatment and structural deformation.
The efficient electrocatalytic reduction conversion efficiency of carbon dioxide is achieved at 93.7%, which is more reactive and stable than traditional copper-based MOFs, and does not require additional treatment, and the catalytic performance is significantly improved.
Smart Images

Figure CN119287442A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical catalysis, and specifically relates to an octahedral BIF-29 catalytic material and a continuous preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The overuse of fossil fuels has led to a rapid increase in atmospheric carbon dioxide concentrations, disrupting the natural balance of the carbon cycle. This has led to global warming, with attendant frequent storms, droughts, and rising sea levels. As climate change intensifies, there is an urgent need to close the carbon cycle by developing advanced technologies to protect the ecological environment. Electrocatalytic reduction of carbon dioxide to value-added chemicals by utilizing renewable electricity offers a practical solution to offset the additional carbon footprint. However, the disruption of the symmetrical linear structure brings about a high activation energy barrier and the stability of the C=O bond (750 kJ mol -1 ), making electrochemical processes challenging. The inherently sluggish kinetics of these reactions highlight the crucial role of electrocatalysts. In this regard, researchers and governments around the world have paid great attention to the field of energy conversion and storage materials over the past few decades.
[0004] Metal-organic frameworks (MOFs) are ideal materials due to their extraordinary structural versatility, synthetic tunability, ultrahigh porosity, and high surface area. MOFs are crystalline structures composed of inorganic metal ions and organic ligands, which can be synthesized by bottom-up assembly methods under solvothermal conditions. To date, many MOFs have been widely used in batch applications such as heterogeneous catalysis, gas energy storage (H2 and CH4), CO2 capture, separation, and reduction reactions. However, the insulating nature (lack of electrical conductivity) of most existing MOFs limits their successful application in electrocatalysis, which is at the core of applications in energy storage and power generation. Summary of the invention
[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an octahedral BIF-29 catalytic material and a continuous preparation method and application thereof. The octahedral BIF-29 catalytic material proposed in the present invention can be used as a high-efficiency electrocatalytic reduction catalyst for carbon dioxide without carbonization treatment. The octahedral BIF-29 catalytic material is a unique π-π stacking interaction that provides space and orbital overlap for electrons to form a spatial electron transport path. The typical M6L8 structure has six exposed planar mononuclear copper centers, which can maximize the exposure of catalytic active sites, accelerate the approach of reactant molecules to the active sites and the desorption of products, and improve the selectivity of target products.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In the first aspect, the present invention provides an octahedral BIF-29 catalytic material, including a metal copper salt and an organic ligand. The octahedral BIF-29 catalytic material has an M6L8 structure, that is, six metal copper sites are connected to eight organic ligands to form a cage structure, having six exposed mononuclear copper centers, which are connected to the ligands through copper-nitrogen bonds inside, and the microscopic morphology presents an octahedral morphology.
[0008] Furthermore, the diameter of the octahedral BIF-29 catalytic material is 2-5 μm.
[0009] Furthermore, the organic ligand is potassium tri(1H-imidazolyl)borohydride; and the metal copper salt is copper nitrate.
[0010] In a second aspect, the present invention provides a continuous preparation method of the above-mentioned octahedral BIF-29 catalytic material, comprising the following steps:
[0011] Assembling a microfluidic pneumatic continuous reaction device, the microfluidic pneumatic continuous reaction device comprising an A syringe, a B syringe, a C syringe, a reaction tube, a mixer, a heating device and a collecting device, the A syringe is pre-filled with an organic ligand solution, the B syringe is pre-filled with a metal copper salt solution, and the C syringe is pre-filled with gas;
[0012] The organic ligand solution in syringe A and the metal copper salt solution in syringe B are mixed in a mixer to obtain a reaction mixture, and the reaction mixture flows continuously in the reaction tube. The gas in syringe C is used to cut the continuously flowing reaction mixture into plugs of uniform size, and the plugs are the reaction micro-locations; the plugs in the reaction tube flow through a heating device with a set temperature, and the products are collected by a collecting device to obtain.
[0013] Furthermore, in the microfluidic pneumatic continuous reaction device, syringe A and syringe B are respectively connected to the mixer, the mixer and the collecting device are connected through a reaction tube, a heating device is arranged between the mixer and the collecting device, and the reaction tube passes through the heating device; syringe C is connected to the reaction tube, and the connection between syringe C and the reaction tube is located between the mixer and the heating device.
[0014] Furthermore, the microfluidic pneumatic continuous reaction device further comprises a tee, and the C syringe is connected to the reaction tube via the tee;
[0015] Furthermore, the reaction tube is a transparent polytetrafluoroethylene hose;
[0016] Furthermore, the inner diameter of the reaction tube is 1-3 mm, the outer diameter is 2-4 mm, and the difference between the outer diameter and the inner diameter is greater than 0.5 mm.
[0017] Furthermore, the metal copper salt is copper nitrate; and the organic ligand is potassium tri(1H-imidazolyl)borohydride.
[0018] Furthermore, the molar ratio of the copper element in the metal copper salt to the organic ligand is (0.5-3):1.
[0019] Furthermore, the required gas is selected from any one of argon, nitrogen or air.
[0020] Furthermore, the reaction temperature of the heating device is 60-80°C.
[0021] Furthermore, the organic ligand solution is an organic ligand dissolved in an organic solvent a; preferably, the organic solvent a is at least one of N,N-dimethylformamide and N,N-dimethylacetamide.
[0022] Furthermore, the metal salt solution is a metal copper salt dissolved in an organic solvent b; preferably, the organic solvent b is at least one of acetone, methanol and ethanol.
[0023] Furthermore, the concentration of the metal copper salt solution is 0.1-8 mol / L, and the concentration of the organic ligand solution is 0.05-0.5 mol / L.
[0024] Further, the fluid flow rate in syringe A is 50-200 μL / min, the fluid flow rate in syringe B is 50-200 μL / min, and the fluid flow rate in syringe C is 400-1000 μL / min.
[0025] Furthermore, the ratio of the fluid flow rates in syringe A, syringe B, and syringe C is 1:1:(5-20).
[0026] A third aspect: The present invention provides a working electrode for electrocatalytic reduction of CO2, the working electrode comprising a substrate and a catalyst supported on the substrate; the catalyst is selected from the above-mentioned octahedral BIF-29 catalytic material or the octahedral BIF-29 catalytic material prepared by the above-mentioned continuous preparation method.
[0027] Furthermore, the catalyst loading on the working electrode is 0.1-2 mg / cm 2 ; The substrate is selected from at least one of carbon paper, carbon cloth, and carbon felt.
[0028] In a fourth aspect, the present invention provides an application of the above-mentioned octahedral BIF-29 catalytic material or the octahedral BIF-29 catalytic material prepared by the above-mentioned continuous preparation method or the above-mentioned working electrode in the electrocatalytic reduction of CO2.
[0029] In a fifth aspect, the present invention provides a method for electrocatalytic reduction of CO2, wherein the above-mentioned octahedral BIF-29 catalytic material is mixed with an organic solvent to obtain a dispersion, which is sprayed on a substrate, and after drying, is placed in an electrolytic cell, and carbon dioxide is introduced for electrocatalytic reaction.
[0030] The beneficial effects of the present invention are:
[0031] 1. The present invention provides an octahedral BIF-29 catalytic material, which has an octahedral morphology as a whole and a diameter of 2-5 μm. The octahedral BIF-29 catalytic material is a typical M6L8 structure with six exposed mononuclear copper centers, which can expose the catalytic active sites to the maximum extent, accelerate the approach of reactant molecules to the active sites and the desorption of products, and improve the selectivity of target products. The strong copper-nitrogen bond ensures the stability of the catalyst during the reaction, avoids the aggregation of metal particles in the catalytic process due to the reaction, and has a high reuse rate.
[0032] 2. When the organic ligand is potassium tri(1H-imidazolyl)borohydride and the metal copper salt is copper nitrate, the prepared BIF-29 catalytic material having a typical M6L8 structure has a strong reactivity. When the octahedral BIF-29 catalytic material participates in the electrocatalytic carbon dioxide reduction reaction, its electrocatalytic carbon dioxide reduction conversion efficiency is as high as 93.7%.
[0033] 3. Compared with the traditional copper-based MOFs material, the octahedral BIF-29 catalytic material obtained by the present invention can be directly used as a catalyst for the electrocatalytic carbon dioxide reduction reaction without other treatments (such as heat treatment, etc.), and the structure of the catalyst does not change before and after the reaction. In addition, the octahedral BIF-29 catalytic material prepared by the present invention has better catalytic performance (carbon dioxide conversion rate 93.7%) than the traditional copper-based MOFs material (carbon dioxide conversion rate 55.3%) in the electrocatalytic carbon dioxide reduction reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0035] Figure 1 This is a schematic diagram of the structure of a pneumatic continuous reaction device according to Example 1 of the present invention, including a reaction pipeline, a syringe A, a syringe B, a syringe C, a mixer, a reaction zone, and a collection device;
[0036] Figure 2 The structure diagram of the octahedral BIF-29 catalytic material prepared in Example 2 of the present invention includes metal copper connected to nitrogen in an organic ligand to form a micro two-dimensional planar structure;
[0037] Figure 3 The X-ray powder diffraction pattern (PXRD) of the octahedral BIF-29 catalytic material prepared in Example 2 of the present invention;
[0038] Figure 4 This is a scanning electron microscope (SEM) image of the octahedral BIF-29 catalytic material prepared in Example 2 of the present invention;
[0039] Figure 5 This is a transmission electron microscope (TEM) image of the octahedral BIF-29 catalytic material prepared in Example 2 of the present invention;
[0040] Figure 6 The X-ray powder diffraction pattern (PXRD) of the octahedral BIF-29 catalyst material prepared in Example 2 of the present invention before and after spraying on the gas diffusion layer reaction;
[0041] Figure 7 This is a scanning electron microscope (SEM) image of the octahedral BIF-29 catalyst material prepared in Example 2 of the present invention before being sprayed on the gas diffusion layer for reaction;
[0042] Figure 8 This is a scanning electron microscope (SEM) image of the octahedral BIF-29 catalytic material prepared in Example 2 of the present invention after spraying on the gas diffusion layer for reaction;
[0043] Fig. 9 This is a scanning electron microscope (SEM) image of the octahedral BIF-29 catalyst material prepared in Example 3 of the present invention;
[0044] Fig.10 This is a transmission electron microscope (TEM) image of the octahedral BIF-29 catalytic material prepared in Example 3 of the present invention;
[0045] Fig.11 This is a scanning electron microscope (SEM) image of the octahedral BIF-29 catalytic material prepared in Example 4 of the present invention;
[0046] Fig.12 The X-ray powder diffraction pattern (PXRD) of the material obtained in Comparative Example 1 of the present invention;
[0047] Fig.13 The X-ray powder diffraction pattern (PXRD) of the material obtained in Comparative Example 2 of the present invention;
[0048] Fig.14 This is a scanning image of the traditional Cu-MOF in Comparative Example 3 of the present invention;
[0049] Fig.15 It is a selectivity diagram of different applied potentials in a flow-type electrolytic cell in an application example of the present invention. DETAILED DESCRIPTION
[0050] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0051] All the raw materials in the examples are conventional reagents and commercially available products and were used directly without further purification.
[0052] Example 1
[0053] This embodiment provides the assembly of a microfluidic pneumatic continuous reaction device, such as Figure 1 The microfluidic pneumatic continuous reaction device includes an A syringe, a B syringe, a C syringe, a first injection tube, a second injection tube, a mixer, a tee, a third injection tube, an oven, a reaction tube and a collecting device. The first injection tube, the second injection tube, the third injection tube and the reaction tube are all transparent polytetrafluoroethylene hoses with an inner diameter of 2 mm and an outer diameter of 3 mm.
[0054] The A syringe is connected to the mixer through the first injection tube, the B syringe is connected to the mixer through the second injection tube, the mixer and the collecting device are connected through the reaction tube, an oven is arranged between the mixer and the collecting device, and the reaction tube passes through the oven; the oven is an electric constant temperature blast drying oven, which is used to heat the reaction tube. The C syringe is connected to the third injection tube, and the third injection tube is connected to the reaction tube through a tee, and the tee is located between the mixer and the heating device.
[0055] Example 2
[0056] This embodiment provides a method for continuously preparing an octahedral BIF-29 catalytic material, using the microfluidic pneumatic continuous reaction device of Example 1, and the specific steps are as follows:
[0057] Step 1, connecting syringe A, syringe B, syringe C, a mixer and an oven in sequence through a reaction pipeline;
[0058] Step 2: dissolve 0.825 g KBH(im)3 ligand in 30 mL N,N-dimethylacetamide and add it to syringe A; dissolve 1.875 g copper nitrate trihydrate in 30 mL methanol and add it to syringe B; add high-purity nitrogen gas into syringe C.
[0059] Step 3: The reaction temperature of the oven is 70°C.
[0060] Step 4, set the flow rate of syringe A to 100 μL / min, the flow rate of syringe B to 100 μL / min, and the flow rate of syringe C to 600 μL / min. The flow rate ratio of syringe A, syringe B, and syringe C is approximately 1:1:6; first, the organic ligand solution and the metal Cu salt solution in syringe A and syringe B are mixed in a mixer to obtain a reaction mixed solution, and the nitrogen in syringe C is used to cut the continuously flowing reaction liquid into uniformly sized plugs, which are the reaction micro-locations.
[0061] Step 5: Collect the product using a product collection device in the microfluidic pneumatic continuous reaction, separate the product by centrifugation or filtration, and obtain the octahedral BIF-29 catalytic material.
[0062] Figure 2 The structure diagram of the obtained octahedral BIF-29 catalytic material includes metal copper connected to nitrogen in organic ligands to form a micro two-dimensional planar structure; the octahedral BIF-29 catalytic material includes metal copper salt and organic ligands, and the octahedral BIF-29 catalytic material is an M6L8 structure, that is, six metal copper sites are connected to eight organic ligands to form a cage structure with six exposed mononuclear copper centers, which are connected to the ligands through copper-nitrogen bonds inside, and the microscopic morphology presents an octahedral morphology.
[0063] Figure 3 This is the PXRD spectrum of the obtained BIF-29 catalytic material. It can be seen that the BIF-29 catalytic material is consistent with the XRD simulation peak, proving that the material was successfully synthesized.
[0064] Figure 4 This is the SEM image of the BIF-29 catalytic material. It can be seen that the BIF-29 catalytic material has an octahedral morphology with a diameter of about 5-8μm.
[0065] Figure 5 This is the TEM image of BIF-29 catalytic material, confirming the octahedral structural characteristics of the material.
[0066] Example 3
[0067] The difference from Example 2 is that the organic solvent in which the organic ligand in step 2 is dissolved is different.
[0068] In this embodiment, in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylformamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of methanol and added to syringe B; high-purity nitrogen is added to syringe C.
[0069] Fig. 9 This is the SEM of BIF-29 catalytic material.
[0070] Fig.10 TEM of BIF-29 catalytic material.
[0071] Example 4
[0072] The difference from Example 2 is that the metal copper salt in step 2 is dissolved in a different organic solvent.
[0073] In this embodiment, in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylacetamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of ethanol and added to syringe B; high-purity nitrogen gas is added to syringe C.
[0074] Fig.11 This is the SEM image of BIF-29 catalytic material.
[0075] Example 5
[0076] The difference from Example 2 is that the organic solvents in which the organic ligand and the metal copper salt are dissolved in step 2 are different.
[0077] In this embodiment, in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylformamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of ethanol and added to syringe B; high-purity nitrogen gas is added to syringe C.
[0078] Example 6
[0079] The difference from Example 2 is that the gas in the syringe C in step 2 is different.
[0080] In this embodiment, in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylacetamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of methanol and added to syringe B; and air is added to syringe C.
[0081] Example 7
[0082] The difference from Example 2 is that the gas in the syringe C in step 2 is different.
[0083] In this embodiment, in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylacetamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of methanol and added to syringe B; argon gas is added to syringe C.
[0084] Comparative Example 1-Different Metal Copper Salts
[0085] In this comparative example, the specific steps are the same as those in Example 2, except that in step 2, 0.825 g of KBH(im)3 ligand is dissolved in 30 mL of N,N-dimethylacetamide and added to syringe A; 1.41 g of copper acetate is dissolved in 30 mL of methanol and added to syringe B; and argon gas is added to syringe C.
[0086] Among them, the final prepared material cannot form an octahedral morphology, such as Fig.12 As shown, the XRD diffraction peaks of the material do not correspond to the simulated peaks.
[0087] Comparative Example 2 - Different organic ligands
[0088] In this comparative example, the specific steps are the same as those in Example 2, except that in step 2, 0.160 g of 1,3,5-benzenetricarboxylic acid ligand is dissolved in 30 mL of N,N-dimethylacetamide and added to syringe A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of methanol and added to syringe B; and high-purity nitrogen gas is added to syringe C.
[0089] Among them, the final prepared material morphology is octahedral, such as Fig.13 As shown, if the XRD diffraction of the material matches the highest peaks of the simulation peaks, then it is an octahedral material.
[0090] Comparative Example 3-Traditional Cu-MOF
[0091] This comparative example provides a method for preparing traditional Cu-MOF using a traditional solvothermal method.
[0092] Step 1: First, 0.160 g of 1,3,5-benzenetricarboxylic acid ligand is dissolved in 30 mL of methanol, which is referred to as solution A; 1.875 g of copper nitrate trihydrate is dissolved in 30 mL of methanol, which is referred to as solution B; solution A and solution B are mixed and stirred for five minutes, and then transferred into a reactor.
[0093] Step 2: Set the oven temperature to 80°C for 10 hours; place the reactor in the oven with the programmed temperature set, wait for the reaction to be completed, and cool down naturally.
[0094] Step three, collecting the products after the reaction, separating the products by centrifugation, and obtaining the traditional Cu-MOF.
[0095] Fig.14 This is the SEM image of the obtained traditional Cu-MOF catalyst. It can be seen that the traditional Cu-MOF material also presents an octahedral morphology with a diameter of about 1 μm.
[0096] Application examples:
[0097] The octahedral BIF-29 catalytic material prepared in Example 2 was applied to the electrochemical carbon dioxide reduction reaction. The electrolytic cell used was a flow-type electrolytic cell, which consisted of three parts: a gas flow path, a cathode cell, and an anode cell. Each part was sealed by a polytetrafluoroethylene gasket. The cathode cell and the anode cell were separated by a Formazan FAB-PK-130 ion exchange membrane. The gas diffusion carbon paper used was YLS-30T. The electrolyte used 1M KOH, and the carbon dioxide gas introduced was high-purity carbon dioxide. The specific steps are as follows:
[0098] First, 10 mg of the octahedral BIF-29 catalytic material prepared in Example 2 was added to a mixed solution of 1 mL of isopropanol and 50 μL of perfluorosulfonic acid resin (Nafion, 5 wt.%), followed by ultrasonic treatment for 30 minutes to obtain a uniformly dispersed solution; then, 200 μL of the dispersion was transferred to a spray gun and evenly sprayed on a 2*2 gas diffusion carbon paper to obtain a catalytic material loading of about 0.5 mg cm -2 , the prepared diffusion layer was transferred into a glove box overnight to completely dry it; then the prepared gas diffusion layer was assembled between the gas chamber and the cathode electrolyte chamber of the flow-type electrolytic cell.
[0099] The assembled flow-type electrolytic cell was tested for the performance of the electrocatalytic carbon dioxide reduction reaction. Before the reaction, the carbon dioxide was introduced at a flow rate of 30 mL / min and the electrolyte was introduced at a flow rate of 20 mL / min. The products were analyzed by Shimadzu GC-2014 gas chromatography, and the selectivity of the electrocatalytic carbon dioxide reduction reaction was calculated according to formula (I). Figure 6 PXRD spectra of octahedral BIF-29 catalyst material sprayed on gas diffusion carbon paper before and after reaction; Figure 7-8 SEM images of octahedral BIF-29 catalyst material sprayed on gas diffusion carbon paper before and after reaction; thanks to the unique micro two-dimensional planar Cu-N4 structure (such as Figure 2 As shown in Figure 2, carbon dioxide molecules can be adsorbed on copper active sites with lower adsorption energy, making the BIF-29 catalytic material exhibit excellent catalytic performance in the electrocatalytic carbon dioxide reduction process. Fig.13 The carbon dioxide selectivity under different applied potentials is shown, and Table 2 gives the specific selectivity of carbon dioxide reduction under different applied potentials. It can be seen that the octahedral BIF-29 catalytic material has a high carbon dioxide conversion performance at -1.2v~-1.4v, and the total conversion performance exceeds 90%.
[0100] Formula (I):
[0101]
[0102] Where n x is the amount of substance of product x (mol), N is the number of electrons transferred when generating product x (N is 2 when the product is CO, H2 and formate), F is the Faraday constant (96485C mol -1 ), Q is the amount of charge (C) that produces x transfer.
[0103] Experimental results and performance analysis
[0104] Octahedral BIF-29 catalyst materials were prepared according to the examples and comparative examples for electrocatalytic carbon dioxide reduction reaction, and the reaction activities of different catalyst materials were investigated, as shown in Table 1.
[0105] Table 1
[0106] Example Carbon dioxide conversion rate (%) Example 2 93.7 Example 3 84.6 Example 4 83.7 Example 5 86.4 Example 6 80.5 Example 7 83.2 Comparative Example 1 \ Comparative Example 2 45.2 Comparative Example 3 55.3
[0107] Among them, the "\" in Table 1 means not detected. Due to the difference in the metal copper salt in Comparative Example 1, the octahedral material was not finally synthesized, and the electrocatalytic carbon dioxide reduction reaction of the material was not carried out. In Comparative Example 2, due to the difference in organic ligands, when the ligand is 1,3,5-benzenetricarboxylic acid ligand, although an octahedral material is formed, its catalytic performance is not as good as that of the embodiment of the present invention. The traditional Cu-MOF material prepared by the traditional solvothermal method in Comparative Example 3 is an octahedral material, but its catalytic performance is also not as good as that of the embodiment of the present invention.
[0108] The octahedral BIF-29 catalytic material prepared in Example 2 was used for electrocatalytic carbon dioxide reduction reaction, and the reaction activity of the catalytic material at different potentials was investigated, as shown in Table 2.
[0109] Table 2
[0110]
[0111]
[0112] The conditions of the electrocatalytic carbon dioxide reduction reaction are as follows: a carbon dioxide introduction rate of 30 mL / min, an electrolyte introduction rate of 20 mL / min, the reaction is carried out at room temperature, and the gas phase product is analyzed by chromatography after the reaction is carried out for ten minutes.
[0113] From the above carbon dioxide reduction comparison, it can be seen that when the organic ligand is potassium tri(1H-imidazolyl)borohydride and the metal copper salt is copper nitrate, the BIF-29 catalytic material with a typical M6L8 structure prepared by the present invention has a strong reactivity. Therefore, the typical M6L8 structure of the octahedral BIF-29 catalytic material prepared by the present invention has six exposed mononuclear copper centers at the periphery of the structure, which is conducive to the exposure of catalytic active sites, promotes the adsorption and activation process of carbon dioxide at the catalytic active sites, and thus greatly improves the catalytic performance of the catalyst.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An octahedral BIF-29 catalytic material, characterized in that: It includes metal copper salt and organic ligand. The octahedral BIF-29 catalytic material has an M6L8 structure, that is, six metal copper sites are connected with eight organic ligands to form a cage-like structure with six exposed mononuclear copper centers, which are connected to the ligands through copper-nitrogen bonds inside, and the microscopic morphology presents an octahedral morphology.
2. The octahedral BIF-29 catalytic material according to claim 1, characterized in that: The diameter of the octahedral BIF-29 catalytic material is 2-5 μm.
3. The octahedral BIF-29 catalytic material according to claim 1, characterized in that: The organic ligand is potassium tri(1H-imidazolyl)borohydride; the metal copper salt is copper nitrate; The molar ratio of the copper element in the metal copper salt to the organic ligand is (0.5-3):
1.
4. The continuous preparation method of the octahedral BIF-29 catalytic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Assembling a microfluidic pneumatic continuous reaction device, the microfluidic pneumatic continuous reaction device comprising an A syringe, a B syringe, a C syringe, a reaction tube, a mixer, a heating device and a collecting device, the A syringe is pre-filled with an organic ligand solution, the B syringe is pre-filled with a metal copper salt solution, and the C syringe is pre-filled with gas; The organic ligand solution in syringe A and the metal copper salt solution in syringe B are mixed in a mixer to obtain a reaction mixture, and the reaction mixture flows continuously in the reaction tube. The gas in syringe C is used to cut the continuously flowing reaction mixture into plugs of uniform size, and the plugs are the reaction micro-locations; the plugs in the reaction tube flow through a heating device with a set temperature, and the products are collected by a collecting device to obtain.
5. The continuous preparation method according to claim 4, characterized in that: In the microfluidic pneumatic continuous reaction device, the A syringe and the B syringe are respectively connected to the mixer, the mixer is connected to the collecting device through a reaction tube, a heating device is arranged between the mixer and the collecting device, and the reaction tube passes through the heating device; the C syringe is connected to the reaction tube, and the connection between the C syringe and the reaction tube is located between the mixer and the heating device; Preferably, the microfluidic pneumatic continuous reaction device further comprises a tee, and the C syringe is connected to the reaction tube via the tee; Preferably, the reaction tube is a transparent polytetrafluoroethylene hose; Preferably, the reaction tube has an inner diameter of 1-3 mm, an outer diameter of 2-4 mm, and a difference between the outer diameter and the inner diameter of more than 0.5 mm.
6. The continuous preparation method according to claim 4, characterized in that: The metal copper salt is copper nitrate; the organic ligand is potassium tri(1H-imidazolyl)borohydride; Preferably, the molar ratio of the copper element in the metal copper salt to the organic ligand is (0.5-3):1; Preferably, the gas is selected from any one of argon, nitrogen or air; Preferably, the reaction temperature of the heating device is 60-80°C; Preferably, the organic ligand solution is an organic ligand dissolved in an organic solvent a; further preferably, the organic solvent a is at least one of N,N-dimethylformamide and N,N-dimethylacetamide; Preferably, the metal salt solution is a metal copper salt dissolved in an organic solvent b; further preferably, the organic solvent b is at least one of acetone, methanol, and ethanol; Preferably, the concentration of the metal copper salt solution is 0.1-8 mol / L, and the concentration of the organic ligand solution is 0.05-0.5 mol / L; 7. The continuous preparation method according to claim 4, characterized in that: The fluid flow rate in syringe A is 50-200 μL / min, the fluid flow rate in syringe B is 50-200 μL / min, and the fluid flow rate in syringe C is 400-1000 μL / min; The ratio of the fluid flow rates in syringe A, syringe B, and syringe C is 1:1:(5-20).
8. A working electrode for electrocatalytic reduction of CO2, characterized in that: The working electrode comprises a substrate and a catalyst supported on the substrate; the catalyst is selected from the octahedral BIF-29 catalytic material according to any one of claims 1 to 3 or the octahedral BIF-29 catalytic material prepared by the continuous preparation method according to any one of claims 4 to 8.
9. Use of the octahedral BIF-29 catalytic material according to any one of claims 1 to 3, or the octahedral BIF-29 catalytic material prepared according to the continuous preparation method according to any one of claims 4 to 8, or the working electrode according to claim 9 in electrocatalytic reduction of CO2.
10. A method for electrocatalytic reduction of CO2, characterized in that: The octahedral BIF-29 catalytic material according to any one of claims 1 to 3 is mixed with an organic solvent to obtain a dispersion, which is sprayed on a substrate, and after drying, is placed in an electrolytic cell, and carbon dioxide is introduced to perform an electrocatalytic reaction.
Citation Information
Patent Citations
Nanoreactor, and preparation method and application thereof
CN113737208A
Preparation method and application of cobalt-doped cuprous oxide / copper heterostructure catalyst
CN117070994A
Two-dimensional Cu-MOF nanosheet and continuous synthesis method and application thereof
CN117339513A
Method of producing isopropanol from electrochemical reduction of carbon dioxide and related copper-based electrocatalysts
US20200255961A1